Light and Scanning Electron Microscopic Evaluation and Effects of Cadmium on the Gills of the Freshwater Fish Labeo rohita - Muthukumaravel, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Light and Scanning Electron Microscopic Evaluation and Effects of Cadmium on the Gills of the Freshwater Fish Labeo rohita